The evaluation in the education of basic motor abilities in water : the balance. Introductory considerations (I) - Sanchez, J. C. C.; Cortell, J. M. (Journal of Human Sport & Exercise, 2007)
This article approaches the knowledge of the balance motor ability in land as the ground basis to introduce, later on, the necessary and specific adaptations to the own characteristics that aquatics have to develop this ability. In a more concrete way, we will stand out how the knowledge of these characteristics or limiting factors of the basic motor ability allow a concretion when establishing the evaluation criteria, which would facilitate the observation and action task of the teacher.